PELAYANAN KESEHATAN TAHANAN PADA KONDISI OVER CROWDED DI RUMAH TAHANAN NEGARA KLAS 1 CIPINANG - Dini Ramayani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
With an overcrowded Penitentiary condition, basic health services for prisoners in the Penitentiary and State Detention Centers are not maximal when the number of prisoners and detainees exceeds the capacity limit, in this case, an inadequate condition of facilities and infrastructure is found, but with an inhibiting factor in the health service process. such as lack of nutrition and calorie intake, but also with health problems for prisoners and detainees. Dense occupancy rates of prisons and remand centers prevent detention and prisons from carrying out the functions of poor health services, even in addition to excessive occupancy rates (over capacity) has an impact on the death rate of prisoners. The purpose of this research itself is to determine the health service effort that can be done to deal with Over Crowded problems that exist in Cipinang Class 1 State Detention Center, this research was conducted using qualitative descriptive research supported by field research in the form of interviews with information. And the results of this study concluded that there were obstacles in the shortage of medical equipment and drugs the imbalance of the number of medical personnel with prisoners.